IMPLEMENTASI AUTHENTIC LEARNING DENGAN MEDIA VIDEO INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS BERITA PADA SISWA KELAS XI AP2 SMK NEGERI 3 SUKAWATI, GIANYAR TAHUN PELAJARAN 2023/2024 - I Gede Yoga Angga Rinada; I Made Adnyana (Widyadari, 2024)
Writing news texts is one of the important learning items to be mastered by students, especially class Gianyar for the 2023/2024 academic year is still relatively low. The aim of this research is to find out whether implementing authentic learning with interactive video media in writing news can improve student abilities and student responses to implementing authentic learning with interactive video media in class XI AP2 students at SMK Negeri 3 Sukawati. This type of research is classroom action research. The subjects of this research were students in class This research uses two cycles and each cycle consists of planning, action, observation, evaluation and reflection. Data collection techniques use test and observation methods. The data processing method uses descriptive statistical methods. The research results show that implementing authentic learning with interactive video media can increase student responses, and implementing authentic learning with interactive video media can improve the ability to write news texts for class XI AP2 students at SMK Negeri 3 Sukawati, Gianyar for the 2023/2024 academic year.